2004
DOI: 10.1179/026708304225019687
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen related failure of steels – a new aspect

Abstract: Recent studies of the characteristics and mechanism of hydrogen related failure in steels are overviewed. Based on an analysis of the states of hydrogen in steels, the role of hydrogen in reducing ductile crack growth resistance is attributed to the increased creation of vacancies on straining. Cases showing the involvement of strain induced vacancies in susceptibility to fracture are presented. The function of hydrogen is ascribed to an increase in the density of vacancies and their agglomeration, rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
203
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(211 citation statements)
references
References 40 publications
4
203
0
4
Order By: Relevance
“…disordering of the GB structure. It is commonly accepted that hydrogen in metals potentially stabilizes the point defects and enhances the generation of non-thermal equilibrium superabundant vacancies as reported by Nagumo et al [23,24], demonstrating a possibility that the agglomeration of those stabilized vacancies can result in the nucleation of microvoids along the GBs. Recently, Lawrence et al investigated the density of vacancies and vacancy clusters in hydrogen pre-charged single crystalline and polycrystalline pure nickel after tensile deformation by means of thermal desorption spectroscopy (TDA) and positron annihilation spectroscopy (PAS), and reported that polycrystalline material showed higher peak temperature in TDS and longer positron lifetime in PAS [25].…”
mentioning
confidence: 99%
“…disordering of the GB structure. It is commonly accepted that hydrogen in metals potentially stabilizes the point defects and enhances the generation of non-thermal equilibrium superabundant vacancies as reported by Nagumo et al [23,24], demonstrating a possibility that the agglomeration of those stabilized vacancies can result in the nucleation of microvoids along the GBs. Recently, Lawrence et al investigated the density of vacancies and vacancy clusters in hydrogen pre-charged single crystalline and polycrystalline pure nickel after tensile deformation by means of thermal desorption spectroscopy (TDA) and positron annihilation spectroscopy (PAS), and reported that polycrystalline material showed higher peak temperature in TDS and longer positron lifetime in PAS [25].…”
mentioning
confidence: 99%
“…The mechanism of hydrogen diffusion through wear-induced nascent surfaces is supported by researchers who have found hydrogen to have diffused during RCF testing [5,9,[11][12][13] with measured concentrations of between 0.1 and 4.2 ppm [5,9,11], the concentration of hydrogen measured also being proportional to the wear on the steel during sliding tests [9].…”
Section: Introductionmentioning
confidence: 76%
“…Popular mechanisms include hydrogen-enhanced localised plasticity (HELP), hydrogen enhancing the mobility of dislocations ahead of the crack tip resulting in localised plasticity, hydrogen-enhanced decohesion (HEDE), hydrogen increasing lattice strength by a reduction in cohesive binding energy lowering the stress required for cleavage and hydrogen-enhanced strain induces vacancy (HESIV), hydrogen diffusion towards vacancies and nanovoids, their formation being assisted under strain leading to ductile crack growth by localised slip [12,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…According to [16], the increase in their concentration could lead to the increased stability of hydrides in the hydride-forming elements, to the enhancement of metal atom diffusion and, in some cases, to the enhancement of creep. The suggestion about the primary role of hydrogen-induced vacancies in hydrogen-related failure was made by Nagumo et al [17] in the framework of the hydrogen-enhanced straininduced vacancy model [18].…”
Section: Hydrogen Effect On Interaction Between the Lattice Defectsmentioning
confidence: 99%